O estado de exceção no Supremo Tribunal Federal: análise da atuação do Tribunal como poder soberano nos posicionamentos judiciais e extrajudiciais da última década com enfoque na condução do Inquérito no 4781 - Frosi, Tatiana Batista (2022)
This research investigates the progression of casuistry in the decisions of the Supreme Court issued in the last decade, which apex is the Inquiry No. 4781, in order to recognize biopolitical elements that characterize the jurisdictional state of exception, when the Court incorporates the sovereign power to create a hypothetical investigative action without legal foundation through norm suspension. Therefore, the study is divided into tree chapters. The first describes an overview of the Court's decisions over the past ten years on specific topics in which the mechanisms of manipulation of human life emerge as instruments for the delivery of casuist decisions. Those decisions, disconnected from the legal system, escalated to the Inquiry in detail as an unfolding trend existed. The second chapter presents Foucault's biopolitics and its concept of apparatus, as well as Giorgio Agamben's definitions of sovereign power, inclusion-exclusion, force-of-law, “imperium”, and state of exception. In the third chapter, the study articulates the biopower theory with the Court's decisions to demonstrate how the STF considers life in its power calculations to strengthen and preserve the institution while moving away from its institutional duties. The work's methodology consists of an initial bibliographical review of the cited authors, articulated to documental research collected from the STF's electronic portal. The decisions content of the last ten years and the opinions and petitions of the Inquiry no 4781 were the documentation researched. This study employs the method of content analysis, as its starting point is a hypothesis based on an exploratory study and bibliographic and jurisprudential analysis.